2023
DOI: 10.3390/metabo13080893
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites Potentially Derived from Gut Microbiota Associated with Podocyte, Proximal Tubule, and Renal and Cerebrovascular Endothelial Damage in Early Diabetic Kidney Disease in T2DM Patients

Abstract: Complications due to type 2 diabetes mellitus (T2DM) such as diabetic kidney disease (DKD) and cerebral small vessel disease (CSVD) have a powerful impact on mortality and morbidity. Our current diagnostic markers have become outdated as T2DM-related complications continue to develop. The aim of the investigation was to point out the relationship between previously selected metabolites which are potentially derived from gut microbiota and indicators of endothelial, proximal tubule (PT), and podocyte dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In the recent decade, metabolomics has been applied to explore the relationship between blood metabolomic profiling and kidney disease ( 17 ). Several metabolic studies indicated that some metabolites such as tiglylcarnitine, kynurenine, arginine metabolites and tryptophan-related metabolism identified from serum or urine samples may be related with progression of CKD ( 4 , 5 , 18 ). But it is not easy to determine the causal association using cress-sectional or longitudinal observational studies due to high costs for measurements of all blood metabolites and the difficulty in explaining the intrinsic relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent decade, metabolomics has been applied to explore the relationship between blood metabolomic profiling and kidney disease ( 17 ). Several metabolic studies indicated that some metabolites such as tiglylcarnitine, kynurenine, arginine metabolites and tryptophan-related metabolism identified from serum or urine samples may be related with progression of CKD ( 4 , 5 , 18 ). But it is not easy to determine the causal association using cress-sectional or longitudinal observational studies due to high costs for measurements of all blood metabolites and the difficulty in explaining the intrinsic relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites, produced by upstream genes and proteins, may act as important nutrients or harmful products for human health. Previous studies indicated some gut microbiota derived metabolites such as arginine ( 4 ), butenoylcarnitine ( 5 ) and tryptophan metabolism ( 6 ) may participate in the development of chronic kidney disease, underlying the associations between blood metabolites and renal function. Identification of blood metabolites beneficial to renal function may provide novel insight into renal nutrition treatment.…”
Section: Introductionmentioning
confidence: 99%